Prenatal hypoxia leads to hypertension, renal renin-angiotensin system activation and exacerbates salt-induced pathology in a sex-specific manner - S. L. Walton (Nature Portfolio, 2017)
Abstract Prenatal hypoxia is associated with growth restriction and adverse cardiovascular outcomes. Here, we describe renal and cardiovascular outcomes in ageing mouse offspring prenatally exposed to hypoxia (12% O2) from embryonic day 14.5 until birth. At 12 months of age, both male and female offspring exposed to prenatal hypoxia had elevated mean arterial pressure. Glomerular number was reduced by 25% in hypoxia-exposed male, but not female, offspring and this was associated with increased urinary albumin excretion, glomerular hypertrophy and renal fibrosis. Hypoxia-exposed offspring of both sexes were more susceptible to salt-induced cardiac fibrosis, however, renal fibrosis was exacerbated by high salt in males only. In male but not female hypoxia-exposed offspring, renal renin mRNA was increased at weaning. By 12 months, renal renin mRNA expression and concentrations were elevated in both sexes. mRNA expression of At 1a R was also elevated in male hypoxia-exposed offspring at 12 months. These results demonstrate that prenatal hypoxia programs elevated blood pressure and exacerbates salt-induced cardiovascular and renal pathology in a sex specific manner. Given sex differences observed in RAS expression and nephron number, future studies may consider RAS blockade as a therapeutic target in this model.